Immunoglobulin A antibodies to oxidized collagen type II as a potential biomarker for the stratification of spondyloarthritis from rheumatoid arthritis. (3rd July 2020) - Vinci, C; Infantino, M; Raturi, S; Tindell, A; Topping, LM; Strollo, R; Amital, H; Shoenfeld, Y; Gertel, S; Grossi, V; Manfredi, M; Rutigliano, IM; et al.
Abstract : Objectives: The discovery of diseased tissue-specific neoantigens offers the opportunity to develop important disease tissue-specific biomarkers that can help in the prediction, diagnosis, and stratification of diseases. This opportunity is specifically significant for autoimmune diseases where diagnostic biomarkers are not available. Inflammatory autoimmune diseases are commonly associated with local generation of large amounts of reactive oxidants. We have previously identified oxidative post-translationally modified (oxPTM) tissue-specific neoantigens in rheumatoid arthritis (RA) and type 1 diabetes that elicit an immune response. In the current study, we studied the presence and clinical significance of antibodies to oxPTM collagen type II (CII) in patients with spondyloarthritis (SpA). Method: Levels of antibodies specific to native CII and oxPTM-CII were assessed by enzyme-linked immunosorbent assay. Results: Immunoglobulin G (IgG) binding to oxPTM-CII was observed in 52%, 83%, and 28% of serum samples from patients with axial spondyloarthritis (axSpA), RA, and psoriatic arthritis (PsA), respectively. Importantly, while strong IgA anti-oxPTM-CII responses were detected in axSpA and PsA patients, with 47% and 84% respective binders, no IgA anti-oxPTM-CII was detected in RA patients. IgA anti-oxPTM-CII reactivity in axSpA patients treated with biologics was higher and more frequent, with 85% binders compared to 9% binders in patients treated with synthetic disease-modifying anti-rheumatic drugs. Conclusion: Our data imply that SpA and PsA are associated with the presence of antibodies to oxPTM-CII, suggesting that there may be a humoral component that may distinguish patients with SpA from RA. Our approach could be adapted to other diseases, particularly to inflammatory autoimmune diseases.